An AMP-activated protein kinase complex with two distinctive alpha subunits is involved in nutritional stress responses in Trypanosoma cruzi - Sternlieb, Tamara (2021)
Trypanosoma cruzi, the etiological agent of Chagas disease, has a digenetic life cycle. In itspassage from the insect vector to the mammalian host, and vice versa, it must be preparedto cope with abrupt changes in environmental conditions, such as carbon source, pH, temperatureand osmolarity, in order to survive. Sensing and signaling pathways that allow theparasite to adapt, have unique characteristics with respect to their hosts and other free-livingorganisms. Many of the canonical proteins involved in these transduction pathways havenot yet been found in the genomes of these parasites because they present divergenceseither at the functional, structural and/or protein sequence level. All of this makes thesepathways promising targets for therapeutic drugs. The AMP-activated protein kinase(AMPK) is a serine/threonine kinase activated by environmental stresses such as osmoticstress, hypoxia, ischaemia and exercise that results in reduction of ATP and increase ofAMP levels. Thus, AMPK is regarded as a fuel gauge, functioning both as a nutrient and anenergy sensor, to maintain energy homeostasis and, eventually, to protect cells from deathby nutrient starvation. In the present study we report the characterization of AMPK complexesfor the first time in T. cruzi and propose the function of TcAMPK as a novel regulatorof nutritional stress in epimastigote forms. We show that there is phosphotransferase activityspecific for SAMS peptide in epimastigotes extracts, which is inhibited by Compound C andis modulated by carbon source availability. In addition, TcAMPKα2 subunit has an unprecedentedfunctional substitution (Ser x Thr) at the activation loop and its overexpression in epimastigotesled to higher autophagic activity during prolonged nutritional stress. Moreover,the over-expression of the catalytic subunits resulted in antagonistic phenotypes associatedwith proliferation. Together, these results point to a role of TcAMPK in autophagy and nutrient sensing, key processes for the survival of trypanosomatids and for its life cycleprogression.